Blockchain trong giáo dục: kinh nghiệm quốc tế và tiềm năng ứng dụng tại Việt Nam - Hoàng , Sỹ Tương (Tạp chí Giáo dục, 2022)
Blockchain (or distributed ledger), the technology related to Bitcoin cryptocurrency has attracted growing interest from many fields and education is no exception. Recently, Blockchain technology has received considerable attention from educational researchers and educational institutions. This is mainly due to its unique features including decentralization, security, reliability, and data integrity. The question is whether educational institutions will approach Blockchain technologies in a different way from traditional education approaches. The article discusses three Blockchain methods that would pose challenges for educational institutions. The questions are whether Blockchain technologies can help democratize and automate the learning process, reduce training costs, and promote applicability in educational institutions. The purpose of the study is to discuss Blockchain and consider the possibility of applying Blockchain technology in educational institutions as a new digital technology trend.